PATTERN OF SUFISTIC HADITH IN THE CONCEPT OF INSAN KAMIL ABD AL-KARIM AL-JILI - Agung Danarta (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2021)
Philosophical tasawuf is regarded by ahl al-sunnah wa al-jama'ah scholars as the deviation from the Koran and hadith and is considered heretical teaching. Though, in philosophical tasawuf there is doctrine of wahdat al-wujud which is the basis of the theory of Insan kamil which is the theory of perfect human being. The climax of the theory of Insan kamil is one initiated by Abd al-Karim al-Jili. Abd Al-Karim Al-Jili in al-Insan al-Kamil fi Ma'rifah al-Awail wa al-Awakhir gives new ideas related to the development of Insan kamil theory by providing justification of sufistic-oriented hadiths to strengthen the argument of Insan kamil theory. This study analyzes the book al-Insan al-Kamil fi Ma'rifah al-Awail wa al-Awakhir by Abd al-Karim as a primary source to find answers of questions about the concept of insan kamil which was initiated by al-Jili; How did al-Jili position the hadith in the concept of insan kamil; and how was the source, quality of sanad and style of meaning. To achieve this goal, this study uses the structural exegesis method as an analysis tool to find the influence of interpretation of the text with the interpreter's experience in the context that surrounds him. The way Al-Jili responded to the criticism of the ahl al-sunnah wa al-jama'ah scholars related to Philosophical tasawuf is to list and make the hadith of the Prophet as the basis in building the concept of Insan kamil. Generally, the hadiths he used were valid in terms of hadtis methodology accepted by hadits schoolars, only few of them used Sufi hadiths methodology which were not accepted in the hadith scholarly methodology, such as the method of narration through dreams and mukasyafah. Al-Jili built the concept of insan kamil based on the most basic Islamic teachings, namely the pillars of Islam, the pillars of faith, and the teachings of spiritual ethics as a process to reach the level of insan kamil. Al-Jili added spiritual meaning to the various ritual actions he performs. Therefore, al-Jili combined zahir (outer) and bathin (inner) dimensions of worship.Keywords: Insan Kamil, al-Jili, hadith, Sufism